Longing for freedom. Afro-mestizo families from San Juan de la Frontera. (Argentina- 1750-1800) - Donoso Ríos, Ana Laura (Universidad Pedagógica y Tecnológica de Colombia, 2016)
For a slave, acquiring the legal condition for freedom was one of the irst steps needed to reach social mobility in a colonial society. In these processes, the family played an important role by supporting, cooperating and caring for its members. This article addresses the reality of three slave families from the city of San Juan (Argentina) during the second half of the XVIIIth century. The efforts, strategies and resources used by these families to reach freedom for their members are presented in this paper. Based on notarial documents (freedom letters, testaments, notarial certiicates) as well as parochial documents, this study reconstructs the path traversed by these families in their longing for freedom. In the processes observed here, there is evidence of the relevance of certain factors regarding to the decision of the families when freeing one of their members, such as the slave-master relationship, or their ability to gather enough economical resources for the payment.